TEKNOLOGI INFORMASI DALAM MENDOKUMENTASIKAN TUTUR BAHASA NGADHA YANG MENGAJARKAN KODE ETIK TEKS LOKAL - Patrisius Batarius; Watu Yohanes Vianey; Ignatius P. A. N Samane (Jurnal Ilmiah Matrik, 2021)
This research is an answer to the concern about the extinction of the local text code of ethics in an area. These codes of ethics teach the noble values ​​of the local area. The area taken in this study is Ngada in the central part of Flores Island, NTT Province. Research and documentation of Ngadha speech which teaches a code of ethics for local texts is widely carried out. However, this is only known by some people who speak Ngadha. The community in general knows the local language spoken from the local customary activities that have been passed down from generation to generation. Current generations and future generations do not know the meaning and speech of their own local language which contains the education of Pancasila values. Information technology is currently one of the solutions in documenting and publishing Ngadha speech. There are 160 Ngadha language sayings which have Pancasila educational values. These data are collected from interviews that have been written in book form and translated into Indonesian. A website is created to document digitally for further dissemination which is equipped with a literal and figurative meaning. It is hoped that, now and in the future, both elementary and secondary school children will know the meaning and value of Ngadha language speech. Educators can teach local wisdom values ​​in the form of texts to students. Another goal, for academic interests, both in the field of information technology and philosophy, is the moral responsibility of academics in documenting local content in Ngadha language.